Analyzing the resting state functional connectivity in the human language system using near infrared spectroscopy - Molavi, Behnam; May, Lillian; Gervain, Judit; Carreiras, Manuel; Werker, Janet F.; Dumont, Guy A. (Frontiers in Human Neuroscience, 2014)
We have evaluated the use of phase synchronization to identify resting state functional connectivity (RSFC) in the language system in infants using functional near infrared spectroscopy (fNIRS). We used joint probability distribution of phase between fNIRS channels with a seed channel in the language area to estimate phase relations and to identify the language system network. Our results indicate the feasibility of this method in identifying the language system. The connectivity maps are consistent with anatomical cortical connections and are also comparable to those obtained from functional magnetic resonance imaging (fMRI) functional connectivity studies. The results also indicate left hemisphere lateralization of the language network.